Development and thinking of torrential rain forecasting operation in National Meteorological Center - Zechun LI; Yun CHEN; Xidi ZHANG; Yuedong WANG; Kan DAI; Ling ZHANG (暴雨灾害, 2019)
Torrential rain is one of the most important disaster severe weather in China. Forecasting it is not only the key point but also the difficulty in operation. The heavy rain forecasting operation in National Meteorological Center has been developed from the traditional method of subjective extrapolation based on synoptics and statistics on weather map analysis to the modern method of numerical prediction. It is emphasized that the scientific problems of rainstorm forecast are extracted from the practice of forecasting, not from literatures. It is highlighted that forecasters are the initiators of the study on scientific problems of rainstorm and the first participants in solving practical problems. The close combination of forecast and service is an important part of meteorological development with Chinese characteristics, and the important role of National Meteorological Center and the Institute of Heavy Rain and other units in the CMA in rainstorm forecast and research and China's response to sudden natural disasters are fully affirmed. It is clear that the forecast of rainstorm and other disasters is aimed at serving the people, society, economic development and national security. Some perspectives are discussed on how to improve the accuracy of rainstorm forecast from the following aspects:training and improving forecaster's scientific research and practical ability, multi-source observation data application, technology development of mesoscale numerical prediction model and ensemble model, and validation and improvement of revision ability, artificial intelligence technology application.